2011 Fifth International Conference on Innovative Mobile and Internet Services in Ubiquitous Computing 2011
DOI: 10.1109/imis.2011.60
|View full text |Cite
|
Sign up to set email alerts
|

ACSP: A Novel Security Protocol against Counting Attack for UHF RFID Systems

Abstract: Current researches on UHF RFID system security mainly focus on protecting communication safety and information privacy between a pair of specific tag and its corresponding interrogation reader. However, in many scenarios, instead of stealing detailed private information of tags, adversaries aim at estimating the cardinality of tags, which is called counting attack. Unfortunately, most existing protocols are vulnerable to counting attack. To defend against this attack, in this paper we propose ACSP, a novel Ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…C. Chen [ 24 ] proposed Anti-Counting Security Protocol (ACSP) as another lightweight protocol for RFID systems to defend from a counter attack, which is defined as the attacker’s ability to count the number of objects in a system. Safkhani et al [ 25 ] reported ACSP to be vulnerable to major attacks, including the forward/backward traceability attack.…”
Section: Review Of Recent Rfid Authentication Protocolsmentioning
confidence: 99%
“…C. Chen [ 24 ] proposed Anti-Counting Security Protocol (ACSP) as another lightweight protocol for RFID systems to defend from a counter attack, which is defined as the attacker’s ability to count the number of objects in a system. Safkhani et al [ 25 ] reported ACSP to be vulnerable to major attacks, including the forward/backward traceability attack.…”
Section: Review Of Recent Rfid Authentication Protocolsmentioning
confidence: 99%
“…In some special field, the security information must be communicated at high rank security, otherwise, it may cause significant economic loss or security threat. The paper [5] propose an ACSP(anti-counting security protocol) method to employ session identifier and to provide a corresponding authentication metric to verify the commands sent by the reader. To handle counting attack, ACSP periodically updates the session identifier, and securely identifies tags with encryption.…”
mentioning
confidence: 99%